Effects of 3 anesthetics on enkephalins contents in different brain areas of rats - Zhu Yuan-xiang; Chen Jia-jin; Jin Ya-qin; Lu Chang-lin; Lin Bao-cheng; Zhu He-nian; Wu De-lin; He Guang-cai; Lu Yi-xin (Acta Pharmacologica Sinica, 2016)
With radioimmunoassay we studied the effects of 3 anesthetics (urethane, pentobarbital, chloralose) on the contents of leu-enkephalin (LEK) and met-enkephalin (MEK) in 6 areas of brains (hypothalamus, corpus striatum, thalamus, hippocampus, brain stem and cerebral cortex) on 24 male rats. Urethane anesthesia: In all brain areas except corpus striatum, the contents of LEK were significantly reduced. The decreases in hypothalamus and hippocampus were more obvious. The content of MEK was significantly reduced only in hypothalamus. Pentobarbital anesthesia: In 6 brain areas, especially in corpus striatum and hippocampus, the contents of LEK were significantly reduced, whereas the content of MEK was reduced only in hypothalamus. Chloralose anesthesia: In hypothalamus and hippocampus the contents of both enkephalins were significantly reduced. In thalamus only MEK was decreased. The changes in other brain areas were not remarkable.